Bubble phenomenon of ZrB2 based composites at high temperatures. Issue 6 (15th April 2019) - Li, Chong; Niu, Yaran; Liu, Tao; Zhong, Xin; Pan, Xiaohui; Zeng, Yi; Zheng, Xuebin; Ding, Chuanxian
Abstract: Bubble phenomenon is common for ultra-high temperature ceramics (UHTCs) during oxidation or ablation processes, which will impair the oxidation/ablation resistant properties. This work is aiming to illuminate the formation and rupture processes of bubbles. In this work, ZrB2 -SiC-WB composite coatings were prepared via vacuum plasma spray technique and oxidized at 1500 °C for different durations. Obvious bubble phenomenon was observed. The morphology and distribution of bubbles were characterized. The formation mechanism of bubbles was calculated and analyzed based on thermal dynamics. The results showed that B2 O3 gas played a key role in affecting the bubble behaviors. Bubbles tended to nucleate near the interface between the solid and liquid oxide layers. Small bubbles aggregated to large bubbles near the outmost liquid layer. Large bubbles near the surface were easy to rupture. The calculated results were consistent with the observed results.